The Influence of Digital Marketing, Marketing Innovation and Competitor Orientation on the Marketing Performance of Bamboo Crafts MSMEs in Yogyakarta - Fadilah, Erlin; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to determine the influence of digital marketing, marketing innovation, and competitor orientation on the marketing performance of bamboo craft MSMEs in Yogyakarta. By using a questionnaire and a non-probability sampling approach, the research sample consisted of 81 respondents. Based on the Instrument Test findings, the research data turned out to be accurate and genuine. The data in this study was proven to be normally distributed using the Classical Assumption Test which also produced heteroscedasticity and multicollinearity regression models. The research findings show that: (1) Digital marketing has a positive and significant effect on the marketing performance of bamboo craft MSMEs in Yogyakarta. (2) Marketing innovation has a positive and significant effect on the marketing performance of bamboo craft MSMEs in Yogyakarta. (3) Competitor orientation does not have a significant effect on the marketing performance of bamboo craft MSMEs in Yogyakarta.